2010
DOI: 10.1590/s0102-76382010000200016
|View full text |Cite
|
Sign up to set email alerts
|

Desfechos clínicos pós-revascularização do miocárdio no paciente idoso

Abstract: Desfechos clínicos pós-revascularização do miocárdio no paciente idoso Outcomes after coronary artery bypass in aged patientsWork performed at the Heart Institute, Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, São Paulo, SP, Brazil. Results: We analyzed 290 patients that possessed appropriate information. The first group G1, of the patients operated without CPB consisted of 111 patients and the second group G2, of the operated ones with CPB consisted of 179 patients. The univaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…They found that on-pump CABG had a higher mortality rate compared to off-pump CABG (11.5% vs. 2.1%, respectively). However, unlike Iglézias et al [18], they observed a higher incidence of other postoperative complications: stroke (CVA) (11.5% vs. 0%); AF (30.8% vs. 12.8%), AKI (19.2% vs. 0%), respiratory failure (16% vs. 2.1%), dialysis (20% vs. 0%), mechanical ventilation > 24 h (24% vs. 4.3%) and AMI (8% vs. 4.3%) respectively in on-pump vs. off-pump CABG.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…They found that on-pump CABG had a higher mortality rate compared to off-pump CABG (11.5% vs. 2.1%, respectively). However, unlike Iglézias et al [18], they observed a higher incidence of other postoperative complications: stroke (CVA) (11.5% vs. 0%); AF (30.8% vs. 12.8%), AKI (19.2% vs. 0%), respiratory failure (16% vs. 2.1%), dialysis (20% vs. 0%), mechanical ventilation > 24 h (24% vs. 4.3%) and AMI (8% vs. 4.3%) respectively in on-pump vs. off-pump CABG.…”
Section: Discussionmentioning
confidence: 86%
“…Iglézias et al [18] compared the clinical outcomes in patients aged ≥ 80 years undergoing on-pump versus off-pump CABG. They reported an operative hospital mortality rate much higher in on-pump CABG (38%) than in off-pump CABG (11.7%) [18]. However, other postoperative complications were similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coronary artery bypass grafting (CABG) aims to increase survival, to relieve symptoms of myocardial ischemia, to improve ventricular function, to prevent myocardial infarction, to recover the patient physically, psychologically, and socially, as well as to prolong patient's life and QOL [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%